On the best approximation of classes W^r H^ω by algebraic polynomials in the space L_1 - Kogan, A. M. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We obtain an asymptotic equality for the best approximation of the classes W^r H^ω by algebraic polynomials in the space L_1 for convex upwards, regularly varying moduli of continuity.